Pharmacokinetics comparison of two pegylated interferon alfa formulations in healthy volunteers - Marisa Boff Costa; Paulo Dornelles Picon; Guilherme Becker Sander; Hugo Nodarse Cuni; Carmen Valenzuela Silva; Rolando Páez Meireles; Ana Carolina Magalhães Andrade Góes; Nadia Maria Batoreu; Maria de Lourdes de Sousa Maia; Elizabeth Maciel Albuquerque; Denise Cristina de Souza Matos; Pedro Lopez Saura (BMC, 2018)
Abstract Background Several countries have used pegylation technology to improve the pharmacokinetic properties of essential drugs. Recently, a novel interferon alfa-2b protein conjugated to four-branched 12 kDa polyethylene glycol molecules was developed jointly between Cuba and Brazil. The aim of this study was to compare the pharmacokinetic properties of BIP48 (pegylated interferon alfa-2b from Bio-Manguinhos/Fiocruz, Brazil) to those of PEGASYS® (commercially available pegylated interferon alfa-2a from Roche Pharmaceutical). Methods This phase I, single-centre, randomized, double-blind crossover trial enrolled 31 healthy male volunteers aged 19 to 35 who were allocated to two stages, either side of a 5-week wash-out period, with each arm lasting 14 consecutive days after subcutaneous administration of 180 μg of one formulation or the other (study or comparator). The main outcome variable was serum pegylated interferon concentrations in 15 samples collected during the course of the study and tested using an enzyme immunoassay. Results There were no differences between formulations in terms of magnitude or absorption parameters. Analysis of time parameters revealed that BIP48 remained in the body significantly longer than PEGASYS® (Tmax: 73 vs. 54 h [p = 0.0010]; MRT: 133 vs. 115 h [p = 0.0324]; ke: 0.011 vs. 0.013 h(−1) [p = 0.0153]; t1/2: 192 vs. 108 h [p = 0.0218]). Conclusion BIP48 showed the expected pharmacokinetic profile for a pegylated product with a branched molecular structure. Compared to PEGASYS®, the magnitude absorption was similar, but time parameters were consistent with slower elimination. Further studies should be conducted to evaluate the clinical implications of these findings. A phase II-III repeated-dose clinical trial is ongoing to study these findings in patients with chronic hepatitis C virus infection. Trial registration This study is registered on the ClinicalTrials.gov platform (accession number NCT01889849 ). This trial was retrospectively registered in June 2013.